Phonetic Variation Within the Ǹkò̩ró̩ò̩ Speech Community (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Nko̩ro̩o̩ is an Eastern Ijoid language spoken in Rivers state, Nigeria, West Africa. Phonetic variation that correlates with both linguistic and social factors were observed in the speech of speakers from the three sections that make up the Nko̩ro̩o̩ speech community within Opu Nko̩ro̩o̩. The sections include Kpokpo, Otoni-ama, and O̩po̩ro̩kuno̩, divided along the lines of kinship affiliation which serves as the social variable. Data was elicited from competent native speakers from each section via participant observation and with the aid of the SIL comparative African word list and a Marantz digital audio recorder. Word-final lip rounding assimilation, intervocalic consonant deletion, and intra-word and boundary CV syllable deletion were identified as the linguistic variables that affect phonetic variation. The findings revealed that while speakers from Otoni-ama could be identified by lip rounding assimilation, speakers from Kpokpo employed all the deletion processes. These variables served as markers for both sections. Speakers from O̩po̩ro̩kuno̩ represent the unmarked section. No reasons were established for the choices made by each section thus affirming that the relationship between linguistic form and social category is arbitrary. The paper concluded that the variations observed are a pattern of learned speech behavior that aid the expression of group identity as exhibited by each kinship affiliation.